2014
DOI: 10.1002/jctb.4382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different TiO2 samples as photocatalyst for the degradation of a mixture of four commercial pesticides

Abstract: This is the accepted version of the following article: Vicente Candela, R.; Soler Escoda, JM.; Arqués Sanz, A.; Amat Payá, AM.; Frontistis, Z.;Xekoukoulotakis, N.; Mantzavinos, D. (2014)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…In the case of pesticides, TiO 2 has shown better photocatalytic performance than other inorganic semiconductors studied in the catalyzed photodegradation, and TiO 2 nanomaterials have been successfully used for the degradation of several classes of pesticides (see Table 6.4), leading in some cases to complete mineralization (Konstantinou 2003;. Commercially available titania sample Evonik P25 was used to treat a mixture of four commercial pesticides (oxydemeton-methyl, methidathion, carbaryl, and dimethoate) in a pilot plant reactor under natural sunlight leading the quantitative removal of pesticides in less than 300 min; this process was accompanied by a substantial reduction of acute toxicity to Vibrio fischeri (i.e., from an initial value of 50 to 15 %), as well as moderate mineralization, i.e., 40 % chemical oxygen demand (COD) and 25 % dissolved organic carbon (DOC) removal (Vicente et al 2014). The photocatalyzed degradation of s-triazine-type herbicides with suspended and supported TiO 2 has been studied, and it was observed that cyanuric acid is the final photoproduct.…”
Section: Photocatalytic Degradation Of Organic Compounds In the Presementioning
confidence: 99%
“…In the case of pesticides, TiO 2 has shown better photocatalytic performance than other inorganic semiconductors studied in the catalyzed photodegradation, and TiO 2 nanomaterials have been successfully used for the degradation of several classes of pesticides (see Table 6.4), leading in some cases to complete mineralization (Konstantinou 2003;. Commercially available titania sample Evonik P25 was used to treat a mixture of four commercial pesticides (oxydemeton-methyl, methidathion, carbaryl, and dimethoate) in a pilot plant reactor under natural sunlight leading the quantitative removal of pesticides in less than 300 min; this process was accompanied by a substantial reduction of acute toxicity to Vibrio fischeri (i.e., from an initial value of 50 to 15 %), as well as moderate mineralization, i.e., 40 % chemical oxygen demand (COD) and 25 % dissolved organic carbon (DOC) removal (Vicente et al 2014). The photocatalyzed degradation of s-triazine-type herbicides with suspended and supported TiO 2 has been studied, and it was observed that cyanuric acid is the final photoproduct.…”
Section: Photocatalytic Degradation Of Organic Compounds In the Presementioning
confidence: 99%
“…2-Diethylamino-6-methyl-4-hydroxy pyrimidine (DTMHP) is a typical pesticide intermediate widely used in agricultural, i.e., it is the main raw material for the synthesis of diazinon [3] and pirimiphos methyl [4], which are biorefractory and microtoxic. Recently, many methods have been used to treat this kind of wastewater, such as Fenton's reagent [5,6], photocatalysis [7][8][9], biological techniques [10,11] and electrochemical degradation [12,13]. However, Fenton's reagent will produce a large number of chemical sludge.…”
Section: Introductionmentioning
confidence: 98%
“…Although photodegradation of pure active ingredients of pesticides has been the subject of many published papers [1,2,4,5,[18][19][20][21], only several papers focused on degradation of commercial pesticide products [3,[22][23][24][25]. The objective of our investigation was to study and compare the rates of photochemical degradation of the pesticide active ingredient methomyl and its commercial product Lannate-90 (soluble powder-SP).…”
Section: Introductionmentioning
confidence: 99%